Social Media’s Influence on Anti-Sexual Harassment Policies in Egypt (2014-2024)900 - Elleithy, Yasmine (AUC Knowledge Fountain, 2025)
The study examined the role of social media and women’s online activism in the development of anti-sexual harassment policies in Egypt, specifically from 2014 to 2024. Through employing a qualitative research method involving semi-structured, in-depth interviews, the study engaged different actors, including members of the parliament, the National Council for Women, female online activists, and women’s rights specialists. During this time frame, there has been a remarkable shift in the political, social, and legislative landscape, marked by significant restrictions on traditional activism and the enactment of laws addressing sexual harassment. Throughout this period of unprecedented changes, social media has emerged as a pivotal platform for women to voice their concerns and mobilize against sexual harassment, reshaping societal norms and narratives. The research highlights social media’s pivotal role in shaping policy agendas by drawing policymakers’ attention to high-profile cases of sexual harassment and influencing public opinion. Additionally, it accelerates the adoption of pre-existing draft policies, by mobilizing public support for these laws, in addition to reshaping societal norms and narratives. Despite these contributions, the primary driver of policy enactment remains the state’s political will, suggesting a top-down approach in policy making. The study further reveals that policymakers react selectively to digital activism when it aligns with the state’s agenda and norms, often resulting in superficial support for online feminist groups. Policy recommendations include creating direct communication channels between the National Council for Women and female online initiatives, encouraging social media data-driven policies by monitoring sexual harassment and women’s issues on social media, utilizing social media to gather public input during the drafting of laws, and collaborating with social media influencers to disseminate anti-sexual harassment messages.